COMPARISON OF VARIOUS ACTIVE INGREDIENTS BETWEEN EX-SITU AND IN-VITRO GROWN PLANTS OF WITHANIA SOMNIFERA L. AND CICHORIUM INTYBUS L. - K. C. VERMA,; S. SAPRA,; A. BAGGA,; S. K. VERMA, (The Bioscan, 2012)
Different plant parts of two traditional medicinal plants viz. Withania somnifera L. and Cichorium intybus L. were analyzed for their reducing power using Folin-Ciocalteu and Aluminium chloride method respectively. The preliminary phytochemical screenings of various extracts revealed the presence of alkaloids, glycosides, steroids, saponins, tannins and flavonoids and then comparison among these parameters was done in Ex situ and In vitro cultivated plant. Thin layer chromatography (TLC) of alkaloids, flavonoids and terpenoids were carried out with different solvent systems. Among the samples of W. somnifera and C. intybus maximum percentage scavenging activity was observed in methanolic leaf extract. The maximum 2, 2-diphenyl-1-picrylhydrazyl (DPPH) activity was found in the leaf extract. The phenolic content in the above plants ranged from 2 to 10 mg GAE/g while the flavonoid from 3 to 12 mg GAE/g. No direct correlation was found between total phenolic content and antioxidant activity. Dissimilar pattern of antioxidant and phytochemical constitutes of Ex situ and In vitro grown plant was observed.